IMPROVING STUDENTSâ READING COMPREHENSION IN RECOUNT TEXT BY USING SNOWBALL THROWING AT GRADE VIII SMPN 4 PAGARAN TAPAH DARUSSALAM PROVINSI RIAU - Nuryati, Dian; Antoni, Rivi; -, Eripuddin (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This research was Classroom Action Research, this research was conducted at SMPN 4 Pagaran Tapah Darussalam, there were 14 students there, every cycle consisted of meeting with the sequenced activity : Plan, action, Observation and reflection. The teaching learning process was done three stages to follow : pre-activity,whilst âactivity and post-activity. The purpose of this research was to improve students reading comprehension. Researcher used five instruments in collecting the data. Test, Observation sheet, Field note, interview and Video. The result showed that the students score. The conclusion of this research was the students reading comprehension on good category.